PENERAPAN METODE BUSINESS MODEL CANVAS DAN PETA EMPATI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) KEBAB DURIAN UCOK - Yogha Ardwiansyah; Achmad Tjahya Nugraha; Nunuk Adiarni (Niagawan, 2023)
The research explores the development of a business model for UMKM Kebab Durian Ucok using business model canvas analysis, empathy maps, and gap analysis. As an MSME, Kebab Durian Ucok plays an important role in the national economy. Understanding the business model, customer needs, and identifying performance gaps is critical to Kebab Durian Ucok's continued growth and competitiveness.The study begins by providing an overview of the challenges faced by Kebab Durian Ucok as MSMEs in the food industry and emphasizing the importance of strategic planning in business. This study provides an overview and relevance of business model canvas analysis, empathy maps, and gap analysis of business competition.The research framework begins with digging up internal information related to the initial description of the strategy and business model that will produce a value proposition, then an analysis of customer insights with an empathy map is carried out to obtain information from the external side that will produce a customer value proposition, from these results a gap analysis is carried out. The gap is then used as material for evaluating the improvement of the strategy using the new business model canvas.The results obtained are in the form of nine block elements of the UMKM Kebab Durian Ucok canvas business model, the needs and desires of customers consisting of product taste, price suitability, product variety, fresh durian content, texture, and service, as well as the gap between the value proposition and the customer's value proposition. The gap is in the aspects of product attractiveness, information reach, price suitability, and service. The recommended business model strategy is the addition of value proposition, key activities, channels, and key partners element blocks.